Implementasi Pelatihan Digital Marketing Bagi Pelaku UMKM di Kecamatan Sanggatta Utara,Kalimantan Timur - Kaharuddin Kaharuddin; Yurdi Maulidani; Mihani Mihani; Saiful Saiful; Nuridha Matiin (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia's economy but often face challenges in marketing their products, especially in the digital era. This study aims to design and evaluate the effectiveness of digital marketing training for MSME activists in Sangatta District, East Kalimantan. The research methodology uses a mixed-methods approach with 50 MSME actors as subjects. The training conducted includes the basics of digital marketing, the use of social media, content creation, search engine optimization (SEO), and data analysis.The results show a significant increase in participants' knowledge and skills in digital marketing. Additionally, the training successfully increased sales and product visibility of MSMEs. Training participants began adopting digital marketing strategies and using data analytics for more effective decision-making. These positive impacts indicate that digital marketing training can be an effective solution to enhance the competitiveness and sustainability of MSME businesses. This study recommends the implementation of advanced training and continuous support for MSME actors, as well as collaboration between the government, universities, and the private sector to provide necessary resources. Thus, MSMEs in other regions are expected to benefit from similar programs to face challenges in the digital era.